A model of modified meta-iodobenzylguanidine conjugated gold nanoparticles for neuroblastoma treatment. Issue 41 (20th July 2021) - Saimuang, Kween; Suttisintong, Khomson; Kaewchangwat, Narongpol; Thanayupong, Eknarin; Wongngam, Yodsathorn; Charoenphun, Putthiporn; Wanotayan, Rujira; Elaissari, Abdelhamid; Hongeng, Suradej; Polpanich, Duangporn; Jangpatarapongsa, Kulachart
Abstract : 127 I-modified m IBG was successfully synthesized and grafted covalently to the surface of carboxylated PEG-GNPs. The particles were not toxic to the normal fibroblast cells while specifically internalized into neuroblastoma cells line via NET. Abstract : Iodine-131 meta -iodobenzylguanidine ( 131 I- m IBG) has been utilized as a standard treatment to minimize adverse side effects by targeting therapies to bind to the norepinephrine transporter (NET) expressed on 90% of neuroblastoma cells. However, only a minority of patients who receive 131 I- m IBG radiotherapy have clinical responses, and these are usually not curative. In this study, novel ligand-conjugated gold nanoparticles (GNPs) based on m IBG were synthesized and evaluated biologically with neuroblastoma cells in vitro . To induce specific internalization to the tumor cells and utilize it as a model for radioenhancement, 127 I-modified m IBG was successfully synthesized and grafted covalently to the surface of carboxylated PEG-GNPs. 49.28% of the novel m IBG derivative was grafted on carboxylated PEG-GNPs. The particles were stable and not toxic to the normal fibroblast cell line, L929, even at the highest concentration tested (10 13 NPs per mL) at 24, 48, and 72 h. Moreover, the cellular uptake of the model was decreased significantly in the presence of a NET inhibitor, suggesting that there was specific internalization into neuroblastoma cells line (SH-SY5Y) via the NET. Therefore, this model provides useful guidance toward the design of gold nanomaterials to enhance the efficiency of 131 I- m IBG treatment in neuroblastoma patients. However, the investigation of radio-therapeutic efficiency after radioisotope 131 I substitution will be further conducted in a radiation safety laboratory using an animal model.